FLOOD RISK PATTERN RECOGNITION IN KINABATANGAN RIVER, SABAH - NurulSyafiqahZulkefli Mat Yusuf; Ahmad ShakirMohd Saudi; NurZahidah Shafii; Djoko Roespinoedji (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
A flood can be described as any high-water flow in any part of the river system which dominates the natural or artificial banks. In Malaysia, floods frequently occur because of the increase in rainfall rates and rising sea levels in certain parts of the country. This study was conducted to determine the flood risk pattern recognition in Kinabatangan River, Sabah. Thirty years (1989-2019) secondary database obtained from the Malaysian Department of Irrigation and Drainage (DID) Ampang, Kuala Lumpur was statistically analysed using chemometrics techniques. The finding demonstrated that only water level with strong factor loadings (44.82 %) was classified as the most potential contributors of flood occurrence in the research region as it had a good consistency compared to other variables, rainfall and evaporation. From the results, 99% out of total result being classified as High Risk Class with a range of 70 and above risk index, 1% classified as a Cautionary Zone Class with a risk index from 37.14, meanwhile 0% fall into Low Risk Class with a risk index from 0-34. This shown that Kinabatangan River was prone to flood phenomenon. In short, the flood risk index model developed would be a very useful resource for flood mapping and future hazard or risk management prediction, with the engagement of both public and private sectors being key to effective floodplain management